'Excuse Me': Teaching Junior Doctors to Speak Up. Issue 1 (June 2013) - O'Connor, Paul; Byrne, Dara; O'Dea, Angela
A consistent finding in healthcare is that juniors are unwilling to 'speak up' to seniors. Training designed to encourage junior doctors to speak up was designed, delivered, and evaluated. The training was constructed around filmed stories of senior doctors describing situations in which their communication and assertiveness skills were challenged. A total of 110 interns attended the training. The feedback from participants was positive. There was a significant increase in knowledge as a result of the training, and some evidence to support a shift in attitudes in the desirable direction relating to the need to speak-up to seniors. No effect of the training was found on behavior. The results are encouraging in terms of reactions and learning, but further training is required to impact the behavior of junior doctors.